Ne2, a typical CC–NBS–LRR‐type gene, is responsible for hybrid necrosis in wheat. Issue 1 (21st July 2021) - Si, Yaoqi; Zheng, Shusong; Niu, Jianqing; Tian, Shuiquan; Gu, Mengjun; Lu, Qiao; He, Yilin; Zhang, Juan; Shi, Xiaoli; Li, Yiwen; Ling, Hong‐Qing
Summary: Hybrid necrosis, caused by complementary genes Ne1 and Ne2, is a serious barrier for combining desirable traits from different genotypes of wheat, affecting the full utilisation of heterosis. To date, both Ne1 and Ne2 are still not isolated although they were documented decades ago. We report here the map‐based cloning and functional characterisation of Ne2, encoding a coiled coil–nucleotide‐binding site–leucine‐rich repeat (CC–NBS–LRR) protein. Homozygous frameshift mutations generated using the CRISPR/Cas9 approach confirmed the Ne2 ‐inducing hybrid necrosis in wheat. Upregulated expression of Ne2 induced by Ne1 and excess hydrogen peroxide accumulation are associated with the necrosis formation. Genetic analyses of a Ne2 allele ( Ne2 m ) and leaf rust resistance gene LrLC10 / Lr13 revealed that they might be the same gene. Furthermore, we demonstrated that the frequency of the Ne2 allele was much lower in landraces (2.00%) compared with that in modern cultivars (13.62%), suggesting that Ne2 allele has been partially applied in wheat genetic improvement. Our findings open opportunities of thoroughly investigating the molecular mechanism of hybrid necrosis, selecting Lr13 and simultaneously avoiding hybrid necrosis in wheat breeding through marker‐assisted selection.